Community-based ecotourism as a social transformation tool for rural community: A victory or a quagmire? - Velan Kunjuraman; Rosazman Hussin; Roslizawati Che Aziz (Elsevier Ltd., 2022)
This study acknowledges the role of community-based ecotourism as a social transformation tool for local communities in a developing country context. This is a qualitative research study that used in-depth interviews, and field observations were performed and actively involved the pioneers of ecotourism development and community members in the state of Sabah, Malaysia. Through thematic analysis, community-based ecotourism as social transformation tools were identified focusing on economic, socio-cultural, and environmental aspects. The study uncovered that community-based ecotourism has delivered more positive social transformation impacts to the local community than negative ones. Despite the positive impacts of community-based ecotourism on the local community, this study warned that negative impacts of community-based ecotourism may jeopardize the ecotourism’s potential as a social transformation tool for the local community, thus weakening its sustainability. Management implication: The study acknowledged that the community-based ecotourism (CBE) development in the study site has enhanced the livelihood of local communities in terms of economic, socio-cultural, and environmental aspects which contribute to social transformation, thus increasing the value of community ecotourism in rural areas. However, negative social transformation delivered by the ecotourism development still needs to be addressed by the relevant stakeholders to ensure the future sustainability of ecotourism. Rural areas in Sabah are popular for ecotourism due to its abundant natural resources and wildlife attractions. Moreover, local community participation in ecotourism is evident due to the positive impacts of ecotourism to enhance their livelihoods. Thus, the local government should continue to motivate the local community who are participating in the ecotourism development by introducing relevant measures and initiatives. The study highlights several challenges faced by the local community to upskill their knowledge of hospitality and tourism related to CBE. Thus, local tourism policies may emphasize the local community aspiration and development through ecotourism.